Green Marketing and Green Innovation on Green Purchase Intention Through Green Brand Image in Consumer Skincare - Atika Nur Dhyas Putri; Dyah Sugandini; Heru Tri Sutiono (Westscience Press, 2024)
This study aims to determine the influence of green marketing and green innovation on green purchase intention through green brand image. The study is quantitative and a non-probability sampling method with a purposive sampling technique is used to collect primary data through a questionnaire comprised of the demographic profile of the respondents. The population of the study is all the consumers of Avoskin in Special Region of Yogyakarta whose age 17 and over also have concern for the environment. Statistical tests are performed with the help of SmartPLS 3.0 on 113 respondents. The results indicate that partially green marketing and green innovation have a positive and insignificant effect on green purchase intention, but simultaneously green marketing and green innovation have a positive and significant effect through green brand image and green brand image has a positive and significant effect on green purchase intention. This research adds contributions to the social and environmental literature. It can assist managers in developing methods to increase consumers green purchase intention by building a green brand image.